THE PRACTICE OF TAWHID VALUES IN MANAGEMENT DARUSSAADAH HIGH SCHOOL PANGKALAN SUSU SUBDISTRICT LANGKAT - Mesiono, Mesiono; Zaki, Ahmad; Sari, Novita (Universitas Dharmawangsa Medan, 2021)
The problem of this research is not the maximum management of the value of tawhid in Darussaadah High School, Pangkalan Susu District, Langkat regency so that it is necessary to Managemen the value of tawhid value in Darussaadah High School to form kepribadian and student ketauhitan well by the vision and mission of the school. The purpose of this research is to find out how the management of the value of tawhid in Darussaadah High School. The subjects of this study were all students and teachers of Darussaadah High School. This research method uses descriptive qualitative research method about program As for the analysis in this study using descriptive qualitative analysis looking at the behavior process of the subject by the problems examined data analysis is carried out by interviews, observations and documentation studies, techniques of examination of data validity using credibility criteria or degrees of trust, transferability or alienation, Dependability or dependency, Confirmability. Based on the results of the research obtained the results that: Implementation of the concept of Tauhid-based Education in Darussaadah High School, Pangkalan Susu SubDistrict is carried out with the values of tawhid: a. Al-Alaq as the basis for straightening the Akidah (Shahihul Akidah); b. Al-Qolam as the foundation of morality, c. Al-Muzammil as his spiritual provision, d. Al-Muddatsir as the basis for preaching, e. And Allah is all-mighty, all-important. 2. Internalization Measures of The Values of Tauhid Rububiyyah, Uluhiyyah, and Senior High School‟ wa Shifat. 3. The process of internalizing the values of tawhid in Darussaadah High School is formally carried out through Islamic faith learning activities. The subject matter is a forum in teaching the values of the points of tawny based on manhaj salafush sholeh such as the values of Tauhid Rububiyyah, Uluhiyyah, and Senior High School, wa Shifat, 4. In practice, the values of tawhid are more fostered in daily relationships in the dormitory environment